Lipid-based transfection reagents can interfere with cholesterol biosynthesis - Danielli, Mauro (2016)
Lipid-based transfection reagents are widely used for delivery of small interfering RNA into cells. We examined whether the commonly used commercial transfection reagents DharmaFECT-4 and Lipofectamine 2000 can interfere with lipid metabolism by studying cholesterogenesis. Cholesterol de novo synthesis from [14C]acetate was assessed in human hepatocyte-derived Huh-7 cells. The results revealed that DharmaFECT, but not Lipofectamine, markedly inhibited cholesterol biosynthesis by approximately 70%. Cell viability was not significantly altered. These findings suggest that caution is required in the choice of certain lipid-based transfection reagents for gene silencing experiments, particularly when assessing cholesterol metabolism.